Ginkgo biloba extract prescriptions are associated with less frequent repeat visits to ENT doctors due to tinnitus: a retrospective cohort study - Langguth, Berthold; Reineke, Thorsten; Burkart, Martin; Kostev, Karel (Frontiers in Neurology, 2024)
Objectives We aimed to evaluate the drug utilization of Ginkgo biloba extract (Gbe), systemic corticosteroids (CSs), and pentoxifylline (PTXF) for the treatment of acute tinnitus by analyzing electronic patient health record data. In addition, we assessed whether the different drug treatments were associated with different frequencies of repeat visits to ear, nose, and throat (ENT) doctors. Methods This retrospective cohort study used data from the IQVIA Disease Analyzer (DA) database. It included patients with an initial diagnosis of tinnitus between January 2005 and December 2021, treated by ENT specialists in Germany. Results Of 111,629 patients meeting all selection criteria, 51,205 received prescriptions of Gbe, 34,817 of systemic CSs, and 25,607 of PTXF. Gbe prescription was associated with significantly lower odds of a repeat consultation due to tinnitus compared to systemic CSs [odds ratio (OR) 0.91; 95% confidence interval (CI): 0.88–0.95] as well as PTXF (OR 0.74; 95% CI: 0.72–0.77). This association was significant in both men and women and in some age groups. Conclusion Gbe is the most frequently ENT specialist-prescribed drug for the treatment of acute tinnitus. It is associated with a reduced likelihood of patients consulting their ENT specialist for tinnitus again compared to systemic CSs and PTXF.